2021
DOI: 10.1002/chem.202101871
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Octane Number of Naphtha by a Robust and Easily Attainable Metal‐Organic Framework through Selective Molecular Sieving of Alkane Isomers

Abstract: The separation of alkanes, particularly monobranched and dibranched isomers, is of paramount importance in the petrochemical industry for optimizing the feedstock of ethylene production as well as for upgrading the octane number of gasoline. Here, we report the full separation of linear/monobranched alkanes from their dibranched isomers by a robust and easily scalable metal‐organic framework material, Co3(HCOO)6. The compound completely excludes dibranched alkanes but adsorbs their linear and monobranched isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Thus, recent research efforts have been focused on the development of MOFs with ideal pore dimensions that can fully split mono‐ and dibranched isomers. Several MOF‐based adsorbents with such property have been achieved over the past few years, including Al‐bttotb, [11] CAU‐10‐H/Br, [12] HIAM‐302, [13] and others [3, 14] . More recently, [4] we have demonstrated that adsorbents with the capability of splitting mono‐ and di‐branched alkane isomers show notably higher efficiency in the separation of naphtha than those showing thermodynamic separation.…”
Section: Methodsmentioning
confidence: 98%
“…Thus, recent research efforts have been focused on the development of MOFs with ideal pore dimensions that can fully split mono‐ and dibranched isomers. Several MOF‐based adsorbents with such property have been achieved over the past few years, including Al‐bttotb, [11] CAU‐10‐H/Br, [12] HIAM‐302, [13] and others [3, 14] . More recently, [4] we have demonstrated that adsorbents with the capability of splitting mono‐ and di‐branched alkane isomers show notably higher efficiency in the separation of naphtha than those showing thermodynamic separation.…”
Section: Methodsmentioning
confidence: 98%
“…Its adsorption capacities toward nHEX, 2MP, and 3MP are 4.35, 4.11, and 4.26 mmol/g, respectively. These values are much higher than those of MOFs showing selective size exclusion behavior, including Zr-bptc, 14 Al-bttotb, 15 Co-FA, 16 of which the adsorption amounts are ∼2 mmol/g. In contrast, HIAM-202 adsorbs much less dibranched hexane isomers, with uptake capacities of 1.73 and 1.57 mmol/g for 23DMB and 22DMB.…”
mentioning
confidence: 76%
“…Long et al reported the thermodynamic separation of hexane isomers by Fe 2 (BDP) 3 featuring triangular channels. 13 More recently, Li et al developed a series of MOFs, including Zr-bptc, 14 Al-bttotb, 15 Co-FA, 16 and so on, that can either split linear and branched alkanes or separate linear/monobranched and dibranched alkane isomers. However, adsorbents that can separate monobranched and dibranched alkanes with high adsorption capacity are still rare and much needed.…”
mentioning
confidence: 99%
“…It features a three-dimensional (3D) framework containing onedimensional (1D) channels with pore diameter of 5.5 Å (Figure 1), falling right between the molecular sizes of monobranched and dibranched alkanes. [16] The compound was synthesized via solvothermal reactions following reported recipe with modifications. Notably, hundred-gram scale-up synthesis can be easily performed in lab and the materials were characterized by powder X-ray diffraction (PXRD) and thermogravimetric analysis (TGA) (Figure S1-S2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%